The Effectiveness Of Enculturation-Based Anti-Corruption Education In Shaping Students' Character Integrity - Trisakti Handayani (Jurnal Civic Hukum, 2022)
This study aims to: (1) determine the effectiveness of the implementation of enculturation-based anti-corruption education conducted by SMA Negeri 6 Yogyakarta, SMA Negeri 2 Bantul, and SMA Negeri 1 Sleman in curricular and extracurricular ways; and (2) Measuring personal integrity in students as a form of young citizens with integrity in the Special Region of Yogyakarta. This study uses the unbalanced combination method (concurrent embed). There were 16 informants in this study, including the Deputy Principal for Student Affairs, Deputy Principal for Curriculum, PPKn Teachers, and students. The sample in this study were 375 students. The results of the study show that: (1) The implementation of anti-corruption education can be done through curricular and extracurricular activities. The implementation of curricular anti-corruption education is carried out through habituation in learning activities for Civics subjects. The implementation of extracurricular anti-corruption education in its implementation is carried out through extracurricular activities by familiarizing students to practice anti-corruption values ​​in each of their activities. Students in the Special Region of Yogyakarta have personal integrity that is classified as very good. Student integrity score/personal score ≥.1SBx. This shows that students in the Special Region of Yogyakarta are young citizens with integrity.